2021
DOI: 10.2147/jpr.s322432
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Attempts in US Veterans with Chronic Headache Disorders: A 10-Year Retrospective Cohort Study

Abstract: Objectives A large-scale retrospective analysis of veterans with chronic pain was conducted to examine (1) the annual incidence of suicide attempts (SA) in veterans with chronic headache and other chronic pain conditions, and (2) the risk of SA in men and women with chronic headache and chronic headache concurrent with traumatic brain injury (TBI) as compared to non-headache chronic pain. Methods This retrospective study (N=3,247,621) analyzed National Veterans Affair H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 44 publications
(49 reference statements)
0
20
0
Order By: Relevance
“…The 9-item Patient Health Questionnaire (PHQ) is activated if the patient responds to either of two questions in the history (“Little pleasure in doing things”; “Feeling down, depressed, or hopeless”) with “More than half the days” or worse [ 42 ]. Suicide risk: The National Institute of Mental Health’s 4-item ASQ (Ask Suicide Screening Questions) scale is activated after a non-negative response to the PHQ question “Thoughts that you would be better off dead, or of hurting yourself.” Chronic pain is an important risk factor for suicide [ 43 ]: chronic headache posed higher suicide risk than other chronic pain types in a 10-year veterans’ retrospective study [ 44 ]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 9-item Patient Health Questionnaire (PHQ) is activated if the patient responds to either of two questions in the history (“Little pleasure in doing things”; “Feeling down, depressed, or hopeless”) with “More than half the days” or worse [ 42 ]. Suicide risk: The National Institute of Mental Health’s 4-item ASQ (Ask Suicide Screening Questions) scale is activated after a non-negative response to the PHQ question “Thoughts that you would be better off dead, or of hurting yourself.” Chronic pain is an important risk factor for suicide [ 43 ]: chronic headache posed higher suicide risk than other chronic pain types in a 10-year veterans’ retrospective study [ 44 ]. …”
Section: Methodsmentioning
confidence: 99%
“…Suicide risk: The National Institute of Mental Health’s 4-item ASQ (Ask Suicide Screening Questions) scale is activated after a non-negative response to the PHQ question “Thoughts that you would be better off dead, or of hurting yourself.” Chronic pain is an important risk factor for suicide [ 43 ]: chronic headache posed higher suicide risk than other chronic pain types in a 10-year veterans’ retrospective study [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…In 2020, the suicide rate for Veterans was 57.3% greater than for non-Veteran U.S. adults when adjusted for demographic differences ( 9 ). Traumatic brain injury (TBI), PTSD, and depression are significant risk factors for chronic headache in Veterans ( 10 ). Veterans with chronic headache, especially those with comorbid TBI, PTSD, and depression, are at increased risk for suicidal behavior ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Traumatic brain injury (TBI), PTSD, and depression are significant risk factors for chronic headache in Veterans ( 10 ). Veterans with chronic headache, especially those with comorbid TBI, PTSD, and depression, are at increased risk for suicidal behavior ( 10 , 11 ). As such, there is a need to better understand the relationship between suicidality and head, neck, and back pain, and establishing interdisciplinary collaboration when caring for Veterans with migraine, which often go undiagnosed or not coded ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, patients experiencing from pain-related depression and anxiety are also likely to have worse outcomes from chronic pain [ 15 , 16 ]. Numerous studies have also suggested that individuals living with chronic pain are 2 to 3 times more susceptible to suicidal ideation and suicidal behaviors [ 17 - 19 ].…”
Section: Introductionmentioning
confidence: 99%